Numerical calculation of the hydrodynamics of heat carriers, taking into account the dependence of viscosity on temperature - Д.Е. Курманова; Н.Ж.Джайчибеков (Bulletin of L.N. Gumilyov Eurasian National University. Mathematics, computer science, mechanics series, 2022)
The article is devoted to the study of the hydrodynamics of heat carriers in heat exchangers. Given the widespread use of this device, increasing its thermal and hydraulic characteristics has become so important for their designers. In the work, the calculation of non-stationary flows of liquids through the heat exchanger tubes is carried out. Water ("hot" coolant) and oil ("cold" coolant) are used as heat carriers, between which heat exchange occurs through the solid surface of the pipeline, which is the boundary between the heat carriers. When calculating the movement of oil, the fact was taken into account that the dynamic viscosity depends very much on temperature and, depending on temperature, the Reynolds numbers also change. And, as a consequence, when flowing through a sufficiently thin channel, the flow regime changes, namely, the transition from the laminar flow regime to the turbulent one is manifested, while this effect is not observed with the analytical calculation method for constant viscosity. The Reynolds-averaged Navier-Stokes equations, closed using the turbulence model, were used for numerical modeling of fluid dynamics of heat carriers. Verification of the heat exchanger calculations was carried out in the software package "Ansys Fluent".